Sphingomyelinases: their regulation and roles in cardiovascular pathophysiology - Pavoine, Catherine (Oxford University Press, 2009)
Sphingomyelinases (SMases) hydrolyse sphingomyelin, releasing ceramide, and creating a cascade of bioactive lipids. These lipids include sphingosine and sphingosine-1-phosphate, all of which have a specific signalling capacity. SMase activation occurs in different cardiovascular system cell types, namely cardiac myocytes, endothelial and vascular smooth muscle cells, mediating cell proliferation, cell death and contraction of cardiac and vascular myocytes. Three main types of SMases contribute to cardiovascular physiology: the lysosomal and secreted acidic SMases (L- and S-ASMases, respectively) and the membrane neutral SMase (NSMase). These three enzymes have common activators, including ischaemia/reperfusion stress and proinflammatory cytokines, but they differ in their enzymatic properties and subcellular locations which determine the final effect of enzyme activation. This review focuses on the recent advances in the understanding of ASMase and NSMase pathways, and their specific contribution to cardiovascular pathophysiology. Current knowledge indicates that the inhibitors of the different SMase types are potential tools for the treatment of cardiovascular diseases. ASMase inhibitors could be tools against post-ischaemia reperfusion injury, and in the treatment of atherosclerosis. NSMase inhibitors could be tools for the treatment of atherosclerosis, heart failure and age-related decline in vasomotion. However, the design of bioavailable and more specific SMase-type inhibitors remains a challenge.